2x+6-x=(3x+18)

Simple and best practice solution for 2x+6-x=(3x+18) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6-x=(3x+18) equation:


Simplifying
2x + 6 + -1x = (3x + 18)

Reorder the terms:
6 + 2x + -1x = (3x + 18)

Combine like terms: 2x + -1x = 1x
6 + 1x = (3x + 18)

Reorder the terms:
6 + 1x = (18 + 3x)

Remove parenthesis around (18 + 3x)
6 + 1x = 18 + 3x

Solving
6 + 1x = 18 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6 + 1x + -3x = 18 + 3x + -3x

Combine like terms: 1x + -3x = -2x
6 + -2x = 18 + 3x + -3x

Combine like terms: 3x + -3x = 0
6 + -2x = 18 + 0
6 + -2x = 18

Add '-6' to each side of the equation.
6 + -6 + -2x = 18 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = 18 + -6
-2x = 18 + -6

Combine like terms: 18 + -6 = 12
-2x = 12

Divide each side by '-2'.
x = -6

Simplifying
x = -6

See similar equations:

| 9y^22+16=-24y | | (w-9)*(w+4)= | | (5x-4)=(4x-7+1) | | =x+3-15+8x | | 7x^3+7x^2+7x+2=0 | | 32x^2-332x+8=0 | | 6x+8=4(x+9) | | 22=t+17 | | 9x+8x-7x-5x=65 | | 3a=a+26+12 | | 2.5s+2.5=7.5 | | 2.5s+2.4=7.5 | | x(2)+40=180 | | 2(2-j)=(j+10) | | 2(1-x)=6 | | 25=2x-y | | 4x+(2x+18)=180 | | 2x^2-4x-3=27 | | 2d=24+6d | | 8+5(z-4)=2(z+7) | | 7(3-x)=14 | | Py+aye=-4y+8 | | 3v-7v=5 | | 3x^2+23x-8.5=0 | | 8v-6v=4 | | 5(4d+8)=80 | | n(17+x)=34x-r | | 14a+20= | | y-5=28 | | 16x-3=86 | | 4(7t+1)-10=t-(t+5) | | 6(y+5)=-36 |

Equations solver categories